Advanced JavaServer Pages™ - Geary, David (Java 2 platform, enterprise edition series, 2001)
Design and implement flexible, extensible, and maintainable applications with servlets and JSP technology Master powerful authentication and internationalization techniques Learn how to integrate industry-standard XML and XSLT with JSP technology Use JSP technology-based templates to develop robust applications from modular components Advanced JavaServer Pages delivers: Web application design techniques based on JSP and servlets technology Proven strategies for achieving enterprise-class robustness and scalability with JSP technology Expert guidance on implementing JSP technology-based applications with reusable components To fully exploit the power of JavaServer Pages technology in Web application development, based on J2EE technology, you need to master the sophisticated server-side techniques that David Geary presents in Advanced JavaServer Pages . Geary tackles JavaServer Pages technology with the same exhaustive, authoritative approach that made his Graphic Java books into worldwide best sellers. He presents in-depth coverage of advanced topics including: Implementing custom JSP technology tags Designing scalable and extensible Web applications Using authentication to build secure JSP technology-based applications Internationalizing JSP technology-based applications for global environments Advanced JavaServer Pages features detailed chapters on internationalization, authentication, JSP technology templates, design, and XML. It concludes with a comprehensive case study that ties together key topics developed in the book and demonstrates how to integrate advanced techniques based on JSP technology. This book is a must-have resource for every developer of Java technology creating server-side applications with JSP technology and servlets.